Measures of small business success/performance – importance, reliability and usability - Leković, Božidar; Marić, Slobodan M (Industrija, 2015)
The main objective of this paper is to assess the reliability of selected measures of success/performance of small enterprises taking into account all the advantages and disadvantages of objective (traditional, financial) and subjective (personal perception) indicators. The realization of the basic objective will enable removal of doubt in different categories of success / performance of small businesses, which would be a secondary objective of the paper. The research methodology involves the use parametric procedures due to the characteristics of the selected variables and the number of observations in the sample. Univariate ANOVA and Pearson’s coefficient correlation will be the main methods used. The basis of this study consists of data gathered from e-survey of 260 entrepreneurs/ owners/ managers of small enterprises in administrative sub-region of the Republic of Serbia. The analysis results show the correlation between subjective estimate of success of owners/ entrepreneurs/ managers and objective performance indicators, which can be characterized as complementary, meaning that subjective assessment as well as formally stated performance indicators are realistic. In addition, it is important to emphasize as an important result within the group of objective performance indicators, the differences between two groups, financial and non-financial, performance indicators.